Is early initiation of infertility treatment justified in women over the age of 35 years?. Issue 3 (March 2020) - Somigliana, Edgardo; Busnelli, Andrea; Vigano, Paola; Vegetti, Walter; Goisis, Alice; Vercellini, Paolo
Abstract: Research question: Natural fecundity and the success of IVF and intracytoplasmic sperm injection (ICSI) rate both decrease with age. For this reason, in women older than 35 years, it is generally recommended to start the infertility work-up after only 6 months. This assumption, however, may expose couples to over-diagnosis and over-treatment. Design: A theoretical model aimed at assessing the effects of starting the infertility work-up after 6 rather than 12 months of trying to conceive naturally was developed. The assumptions of the model were as follows: infertile women are treated with IVF/ICSI for up to three cycles; IVF/ICSI success rate at first cycle linearly declines with age (3% per year between the ages of 35 and 45 years); the drop-out rate after the first and second cycle is 18% and 25%, respectively; the relative reduction of the success rate at second and third cycle is 16% and 26%, respectively. Results: Early initiation of treatment moderately improved the cumulative chances of live birth resulting from a full IVF/ICSI programme. This improvement is dependent on age. Specifically, it increased from 2.0% at age 35 years to 3.0% at age 43 years. Conversely, the incremental success rate per single IVF cycle was mainly stable, varying only from 1.4% at age 35 years to 1.3% at age 43 years. Conclusions: In women older than 35 years, early initiation of the infertility work-up is associated with only a modest increase in the rate of success of IVF/ICSI. In most scenarios, this advantage may compare unfavourably with the chances of natural conception during the 6-month period.